The Impact of Global Geopolitical Shifts on the Security of Northeast Asia and Mongolia - Purevdorj, Batjargal (Mongolian Journal of International Affairs, 2025)
The current international situation is transforming rapidly, becoming more unstable and unpredictable. Major transitions and changes occurring in international relations and geopolitics. Unfavorable military and political factors have increased at the regional security theaters; therefore, the international security environment has worsened. In the Northeast Asian region, the geopolitical situation caused by the new "Cold War" still prevails. Northeast Asia contains economically developed relatively well-integrated countries but lacks the confidence-building mechanism and security cooperation. Now the Northeast Asian region is considered as the region with the highest probability of armed conflict arising from disputed territorial issues.